Cover crop management strategies for driver weeds in Kansas - Woitaszewski, Lily Anne (Kansas State University, 2023)
Research was conducted in Kansas and other states in the north central region to understand how cover crops influence weed suppression and seedbanks. As cover crops increase on farm production hectares, management strategies must be evaluated to discover which ones result in optimum weed control. The effects of cereal rye cover crop on Palmer amaranth (Amaranthus palmeri S. Watson) and waterhemp (Amaranthus tuberculatus (Moq.) J. D. Sauer) seedbanks were evaluated. Seeds were collected in Kansas, Indiana, Missouri, North Dakota, and Wisconsin. Treatments included burial in cereal rye cover crop and in no cover crop in October of 2021. Seeds were removed in May and October of 2022 and sent to Kansas for viability testing. Seven months after burial, cover crop had no effect on seedbank viability. Twelve months after burial, when analyzing each population individually, Missouri and Indiana waterhemp exhibited greater viability in cover crop than in no cover crop treatments. Kansas Palmer amaranth and waterhemp dormancy was also greater in cover crop compared to no cover crop treatments at all locations. These findings are contrary to our hypothesis that cover crop treatments would increase seedbank decay. In a second study, the effects of grazing on weed suppression were evaluated on three on-farm locations near Castleton, Topeka, and Wabaunsee, Kansas. These three and two other locations including Clay Center and Ellsworth, Kansas were sampled to evaluate forage quality. Weed and cover crop biomass, stocking rate, cattle type, and grazing period varied by location. Near Wabaunsee, where giant foxtail (Setaria faberi Herrm.) and Palmer amaranth were present prior to planting soybean, grazing negatively influenced weed suppression. A reduction in weed suppression was observed when grazing at 1.95 AU ha⁻¹ occurred later in the season. Near Topeka and Castleton, where winter annual weed species such as horseweed (Erigeron canadensis L.), common chickweed (Stellaria media (L.) Vill.), and henbit (Lamium amplexicaule L.) were dominant prior to spring planting, grazing at 1.83 and 3.5 AU ha⁻¹ respectively did not influence weed suppression. These results indicate that farmers should be cautious when allowing cattle to graze cover crops prior to spring planting when summer annual weeds are of concern. These data will provide a basis for further research involving seedbank decay in presence of cover crops as well as grazing cover crops.
Keywords: Cover crop; Weed; Cereal rye; Grazing; Palmer amaranth; Seedbank